Biocatalytic hydroxylation of n-butane with in situ cofactor regeneration at low temperature and under normal pressure - Staudt, Svenja; Müller, Christina A.; Marienhagen, Jan; Böing, Christian; Buchholz, Stefan; Schwaneberg, Ulrich; Gröger, Harald (Beilstein Journal of Organic Chemistry, 2012)
The hydroxylation of n-alkanes, which proceeds in the presence of a P450-monooxygenase advantageously at temperatures significantly below room temperature, is described. In addition, an enzymatic hydroxylation of the “liquid gas” n-butane with in situ cofactor regeneration, which does not require high-pressure conditions, was developed. The resulting 2-butanol was obtained as the only regioisomer, at a product concentration of 0.16 g/L.
Keywords: biotransformations; cofactor regeneration; green chemistry; hydroxylation; P450-monooxygenase